Menumbuhkan nilai-nilai toleransi Dalam bingkai keragaman beragama - Izzan, Ahmad (KALAM, 2017)
The attitude of religious tolerance is an attitude that should be embedded in everyday life and is an empirical reality that must be created on the authority of human beings who have a different religion. Differences in religion is born of a natural process by the will of God. For that plurality is sunnatullah unavoidable. The purpose of this paper is to determine the depth of the concept of religious tolerance that is contained in the Qur'an. As for the verses studied is about pluralism relating to religious tolerance, respect for diversity Syari'ah every religious community, religious freedom, prohibition of intervention in the affairs of other religious beliefs, and cooperation among religions. In doing research on inter-religious tolerance can conclude several things, first to foster the values of tolerance within the framework of religious diversity in fostering religion in general is substantive adhesive used for the harmony of inter-religious relations. Second, in the realm of interpretation differences and diverse religions generate a view that shari'ah of the Prophet Muhammad. is a compilation of the Shari'ah-shari'ah of the Prophet before. Hence the presence of the Shari'ah Prophet Muhammad not deny them, but to collect it into a single solid in one religion (Deen al-Wahid).